2015
DOI: 10.3892/etm.2015.2798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymosin β4 on a rat model of severe acute pancreatitis

Abstract: Abstract. The aim of the present study was to investigate the effects of thymosin β4 on a rat model of severe acute pancreatitis (SAP) induced by sodium taurocholate (STC) and the underlying mechanism. SAP was induced by the retrograde infusion of 5% STC (1 ml/kg) into the bile-pancreatic duct. In certain rats, thymosin β4 (30 mg/kg) was administered intraperitoneally 30 min prior to the infusion of STC. The severity of pancreatitis was evaluated by the measurement of serum amylase, lipase, tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Numerous researchers have endeavored to elucidate the pathogenesis of AP; moreover, the precise molecular mechanisms still need to be understood. Growing evidence suggests that SAP is intricately linked to tissue damage and disturbances in microcirculation, which arise from the release of proinflammatory cytokines and mediators such as TNF-α, IL-1β, IL-6, and intercellular adhesion molecule (ICAM)-1 ( He et al, 2015 ). Experiments have shown that infiltrating inflammatory cells is crucial to experiment-induced AP by producing inflammatory mediators such as IL-1β and monocyte chemoattractant protein-1 (MCP-1) ( Shen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have endeavored to elucidate the pathogenesis of AP; moreover, the precise molecular mechanisms still need to be understood. Growing evidence suggests that SAP is intricately linked to tissue damage and disturbances in microcirculation, which arise from the release of proinflammatory cytokines and mediators such as TNF-α, IL-1β, IL-6, and intercellular adhesion molecule (ICAM)-1 ( He et al, 2015 ). Experiments have shown that infiltrating inflammatory cells is crucial to experiment-induced AP by producing inflammatory mediators such as IL-1β and monocyte chemoattractant protein-1 (MCP-1) ( Shen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%